2009
DOI: 10.1152/ajpendo.00473.2009
|View full text |Cite
|
Sign up to set email alerts
|

Castration differentially alters basal and leucine-stimulated tissue protein synthesis in skeletal muscle and adipose tissue

Abstract: Reduced testosterone as a result of catabolic illness or aging is associated with loss of muscle and increased adiposity. We hypothesized that these changes in body composition occur because of altered rates of protein synthesis under basal and nutrient-stimulated conditions that are tissue specific. The present study investigated such mechanisms in castrated male rats (75% reduction in testosterone) with demonstrated glucose intolerance. Over 9 wk, castration impaired body weight gain, which resulted from a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 60 publications
4
24
0
3
Order By: Relevance
“…Previously, it was shown that castration of male rats increased body fat mass but reduced body lean mass (Jiao et al, 2009). Moreover, steers have lower skeletal muscle mass and higher lipid accumulation than intact bulls (Jeong et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Previously, it was shown that castration of male rats increased body fat mass but reduced body lean mass (Jiao et al, 2009). Moreover, steers have lower skeletal muscle mass and higher lipid accumulation than intact bulls (Jeong et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Although we did not see any changes in Fbxo32 expression in vivo , expression of Fbxo32 was repressed by DHT in myoblasts in vitro . Other orchidectomy studies have shown upregulation of Fbxo32 expression in muscle,1351 with increased muscle protein degradation during atrophy,52 while androgen treatment increases muscle protein synthesis 53. Therefore, it is possible that androgen withdrawal-dependent atrophy occurs in part via the same myogenin-dependent ubiquitin ligase pathways activated in neurogenic atrophy, due to the loss of myogenin and Fbxo32 repression by the AR.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, ex vivo treatment of isolated extensor digitorum longus (EDL) and soleus muscle fiber bundles from elderly female mice (~700 days old) with 2 nM DHT increased rates of protein synthesis (Wendowski, Redshaw et al, 2016). Alternatively, castration did not change rates of protein synthesis in the tibialis anterior (TA) of mice or the gastrocnemius of rats following an overnight fast (Steiner et al, 2016, Jiao, Pruznak et al, 2009). Synthetic rates in the TA were also not different between castrated and sham mice 4 hr following refeeding, nor did castration affect the increase in protein synthesis following a bout of high frequency muscle contractions (Steiner et al, 2016).…”
Section: 1 Androgen Regulation Of Muscle Protein Synthesismentioning
confidence: 99%
“…Synthetic rates in the TA were also not different between castrated and sham mice 4 hr following refeeding, nor did castration affect the increase in protein synthesis following a bout of high frequency muscle contractions (Steiner et al, 2016). Conversely, castration prevented the leucine-induced stimulation of protein synthesis in the gastrocnemius of rats, suggesting mediation of the contributing pathways (Jiao et al, 2009). Several methodological issues may explain the discordant findings between animal studies including the feeding paradigm, model system employed, and muscle or animal species used.…”
Section: 1 Androgen Regulation Of Muscle Protein Synthesismentioning
confidence: 99%
See 1 more Smart Citation